Current methods for detecting ethylene in plants - Cristescu M Simona; Arslanov Denis; Harren J M Frans; Hermans Christian; Mandon Julien; Pessemier De Jerome (Annals of Botany, 2013)
Background: In view of ethylenes critical developmental and physiological roles the gaseous hormone remains an active research topic for plant biologists. Progress has been made to understant the ethylene biosynthesis pathway and the mechanisms of perception and action. Still numerous questions need to be answered and findings to be validated. Monitoring gas production will very often complete the picture of any ethylene research topic. Therefore the search for suitable ethylene measuring methods for various plant samples either in the field, green houses, laboratories or storage facilities is strongly motivated. Scope: This review presents an update of the current methods for ethylene monitoring in plants. It focuses on the three most-used methods - gas chromatography detection, electrochemical sensing and optical detection - and compares them in terms of sensitivity, selectivity, time response and price. Guidelines are provided for proper selection and application of the described sensor methodologies and some specific applications are illustrated of laser-based detector for monitoring ethylene given off by Arabidopsis thaliana upon various nutritional treatments. Conclusions: Each method has its advantages and limitations. The choice for the suitable ethylene sensor needs careful consideration and is driven by the requirements for a specific application.
Keywords: Arabidopsis thaliana; Electrochemical sensing; Ethylene; Gas chromatography; Gas sampling; Laser-based detector